THE EFFECT OF SELF-ESTABLISHMENT AND GROUP PRESSURE ON THE PERFORMANCE OF EMPLOYEES FOR EDUCATIONAL PROFESSIONAL DEVELOPMENT CENTER - Neni Syarifatun NISA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2018)
The purpose of this research was to determine the effect of self-perception and group pressure on the employee performance Professional Development of Educators Center (Pusbangprodik) of the ministry of education and culture. Data was collected through participatory questionnaires. This research uses a survey method with a sample population of 70 people with a quantitative approach. Path analysis was used to analyze inferential and descriptive data. The results of hypothesis testing show that self-perception has a direct effect on performance, group pressure has a direct negative effect on work performance, and self-perception has a direct effect on group pressure. Therefore, to improve the work performance of Pusbangprodik employees, self-perception needs to be improved and group pressure needs to be reduced.